A curricular proposal to implement the English language teaching at the “Centro Infantil Laboratorio Ermelinda Mora”, in students from 3 to 5 years old - Piñeiro Ruiz, Milagro (2011)
The purpose of this article is to describe a project to elaborate and implement an English curriculum for the teachers of third and fourth levels at the Centro Infantil Laboratorio Ermelinda Mora (CILEM) in San Ramón, Alajuela, Costa Rica. In order to determine the type of knowledge that could be expected to be learned during the early stages of approaching a foreign language, the researchers referred to the Multiple Intelligences and Audiolingual Methods, Learning Styles, Learning Strategies, and Listening and Speaking Skills. In addition, the type of research, methodology, data analysis, and conclusions are provided as a tool to guide the reader throughout the research.